2022
DOI: 10.1039/d2ra02108k
|View full text |Cite
|
Sign up to set email alerts
|

Strain engineering of lateral heterostructures based on group-V enes (As, Sb, Bi) for infrared optoelectronic applications calculated by first principles

Abstract: The band gap of the heterojunction decreases with increasing strain and becomes metallic at larger strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The calculated lattice constants for the monolayers As, Sb, and Bi are 3.81 Å, 4.38 Å, and 4.58 Å, respectively. In our previous research within the research group, we evaluated the stability of all structures involved from the perspective of formation energy, demonstrating that the structures can exist spontaneously in a stable manner [ 44 , 45 , 46 ]. After optimization calculation, we found that the most stable adsorption sites of NO and NO 2 molecules on these three materials were located above the interface.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated lattice constants for the monolayers As, Sb, and Bi are 3.81 Å, 4.38 Å, and 4.58 Å, respectively. In our previous research within the research group, we evaluated the stability of all structures involved from the perspective of formation energy, demonstrating that the structures can exist spontaneously in a stable manner [ 44 , 45 , 46 ]. After optimization calculation, we found that the most stable adsorption sites of NO and NO 2 molecules on these three materials were located above the interface.…”
Section: Resultsmentioning
confidence: 99%
“…Strain engineering has already been confirmed to be an effective way to improve the properties of photonic and electronic devices [13,[27][28][29]. In our previous work, the band gaps and band types of As/Sb LHSs have been adjusted by applying tensile or compress strains [23,30,31]. Meanwhile, the adjustment of gas sensing properties is achieved by modifying the surface structure of the substrate material to change the adsorption between the substrate material and the gas.…”
Section: Introductionmentioning
confidence: 99%